Sistema de gestión integral digitalizada de los archivos de la Unidad Educativa Réplica Nicolás Infante Díaz. del cantón Quevedo, provincia de Los Ríos. año 2015. - Gómez Bastidas, Jessica Ximena (2015)
The Educational Unit Replies Nicolás Infante Díaz it is a state institution framed in the Program of Schools of the Millennium led by the Constitutional Government of the Republic of the Ecuador, which should be inmersed in the technological changes that it allows to improve the quality of the service and the institutional image, for what thought about as main objective: "To analyze the necessity to establish the System of Digitized Integral Administration of the archive". The results report that the system of current file doesn't allow to assist quickly and efficiency the requirements of the internal and external users, therefore, it intends the establishment of the software Google Drive in order to provide immediate access to the information and to assist in an opportune way the requirements of the users, in such a way that improves the image of the institution. Keywords: Secretary, archive, documents, digitals.